Oscillatory behaviour of a higher-order dynamic equation - Uçar, Deniz; Bolat Y. (Springer Science and Business Media LLC, 2013)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Dynamic equations on time scales or measure chains; higher-order nonlinear neutral dynamic equation; Oscillating coefficient; Applied Mathematics; Oscillation theory of functional-differential equations; time scale; Discrete Mathematics and Combinatorics; Time scale; oscillating coefficient; Higher-order nonlinear neutral dynamic equation; Analysis